Paths of glory - Archer, Jeffrey
"Some people have dreams that are so magnificent that if they were to achieve them, their place in history would be guaranteed. Francis Drake, Robert Scott, Charles Lindbergh, Amy Johnson, Edmund Hillary, Neil Armstrong, and Lewis and Clark are among such individuals. But what if one man had such a dream, and once he'd fulfilled it, there was no proof that he had achieved his ambition?" "Paths of Glory is the story of such a man - George Mallory. Mallory once told an American reporter that he wanted to climb Mt. Everest, "because it is there." On his third attempt in 1924, at age thirty-seven, he was last seen six hundred feet from the top. His body was found in 1999, and it still remains a mystery whether he ever reached the summit." "But only after you've turned the last page of this novel, inspired by a true story, will you be able to decide if George Mallory's name should be added to the list of legends, in which case another name would have to be removed."